Successful thrombolytic treatment of neonatal arterial thromboses - Stächele, J.; Dinger, J.; Brenner, S.; Hofmann, S. R.; Ifflaender, S.; Knöfler, R. (Hämostaseologie, 2014)
Compared to children of other age groups neonates show an increased thrombotic risk. The acute therapy depends on thrombus age, the localisation of vascular occlusion and the severity of the underlying disease. The treatment of choice is represented by the administration of unfractionated (UFH) or low molecular weight heparin (LMWH). If loss of limbs or organs is imminent, the application of thrombolytic treatment with recombinant tissue-type plasminogen activator (rt-PA) should be considered whilst taking into account the associated bleeding risk. We report on two patients in which thrombolytic therapy has been conducted successfully.
Keywords: Neonates; thrombosis; thrombolytic therapy